2009
DOI: 10.1093/ndt/gfp528
|View full text |Cite
|
Sign up to set email alerts
|

Scoring system for renal pathology in Fabry disease: report of the International Study Group of Fabry Nephropathy (ISGFN)

Abstract: The development of a standardized scoring system of both disease-specific lesions, i.e. lipid deposition related, and general lesions of progression, i.e. fibrosis and sclerosis, showed a spectrum of histologic appearances even in early clinical stage of Fabry nephropathy. These findings support the role of kidney biopsy in the baseline evaluation of Fabry nephropathy, even with mild clinical disease. The scoring system will be useful for longitudinal assessment of prognosis and responses to therapy for Fabry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
149
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 33 publications
6
149
0
12
Order By: Relevance
“…25 In addition, neutralising antibodies directed against agalsidase-beta may be another factor that may limit the success in controlling proteinuria and/ or stabilising renal function. 26 The importance of the age at which ERT is initiated was recently emphasised 12 and is confirmed by the present findings, suggesting that severe underlying changes in renal structure 21 may limit the beneficial effects of controlling urine protein excretion. Regression analysis (table 4) showed that the age at which ERT was started was the only significant factor associated with risk of renal progression in patients for whom ACE inhibitor or ARB therapy controlled the average UPCR to ≤0.5 g/g, thus confirming and extending the recent report from Germain et al…”
Section: Germain Et Alsupporting
confidence: 81%
“…25 In addition, neutralising antibodies directed against agalsidase-beta may be another factor that may limit the success in controlling proteinuria and/ or stabilising renal function. 26 The importance of the age at which ERT is initiated was recently emphasised 12 and is confirmed by the present findings, suggesting that severe underlying changes in renal structure 21 may limit the beneficial effects of controlling urine protein excretion. Regression analysis (table 4) showed that the age at which ERT was started was the only significant factor associated with risk of renal progression in patients for whom ACE inhibitor or ARB therapy controlled the average UPCR to ≤0.5 g/g, thus confirming and extending the recent report from Germain et al…”
Section: Germain Et Alsupporting
confidence: 81%
“…In previous consensus procedures it was agreed that characteristic storage on electron microscopy (EM) of an affected organ (i.e. heart or kidney) should be considered as the gold standard for FD (Fogo et al 2010;Leone et al 2012;Smid 2014;Van der Tol 2014a, b). The panel is convinced that in the group of patients discussed here (i.e.…”
Section: Pathologymentioning
confidence: 99%
“…If correct, this paradigm would greatly enhance research into novel therapeutic approaches to Fabry nephropathy by allowing the extrapolation of concepts from diabetic nephropathy, a better understood and more common disease (Sanchez-Niño et al, 2010b). (Tondel et al, 2008, Fogo et al, 2010, Najafian et al, 2010. There is widespread glycolipid accumulation in glomerular podocytes, mesangial and endothelial cells, as well as proximal and distal tubular cells, interstitial endothelial cells and other endothelial cells.…”
Section: Pathogenesis and Pathologymentioning
confidence: 99%
“…Thus, recent research into the pathogenesis of Fabry nephropathy has focused on the cell biology of the podocyte . The other key pathology feature of Fabry nephropathy is glomerular (glomerulosclerosis) and interstitial fibrosis, which is associated with loss of parenchymal renal cells (podocytes and tubular cells) (Fogo et al, 2010). Thus, there is renewed interest in the link between metabolites accumulated in Fabry disease and the synthesis and deposition of extracellular matrix components.…”
Section: Pathogenesis and Pathologymentioning
confidence: 99%